2008
DOI: 10.1364/ol.33.001672
|View full text |Cite
|
Sign up to set email alerts
|

Controlling a ray bundle with a free-form reflector

Abstract: The problem of controlling a single ray bundle with a single reflector is not generally solvable, but approximate solutions may often be found that are acceptable for applications. We introduce a new technique for finding such approximations and apply it to the design of a driver-side mirror for an automobile that has no blind spot and minimal distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Thus, the challenge is to find shapes that obtain a wide field of view without distorting the image. R. Andrew Hicks [8][9][10][11][12] presents a new technique for finding such approximations and applies it to the design of a rear-view mirror for an automobile that has no blind spot and minimal distortion. With this method, we design a rear-view mirror with a scale factor of 2.…”
Section: Tool Path Generation For Fts Cutting 31 Design Of a Rear-vimentioning
confidence: 99%
“…Thus, the challenge is to find shapes that obtain a wide field of view without distorting the image. R. Andrew Hicks [8][9][10][11][12] presents a new technique for finding such approximations and applies it to the design of a rear-view mirror for an automobile that has no blind spot and minimal distortion. With this method, we design a rear-view mirror with a scale factor of 2.…”
Section: Tool Path Generation For Fts Cutting 31 Design Of a Rear-vimentioning
confidence: 99%
“…Smilie et al 37 fabricated a germanium Alvarez lens for infrared imaging under conditions of modern precision optical manufacturing. Hicks 38 developed a ray-tracing method to obtain a discrete data point cloud for a freeform reflector, which was used to design a 45-deg field of view and a lower-distortion driver-side mirror to effectively increase the driver's field of view. Zhu et al 39 presented a direct design method to obtain a discrete data point cloud, which was fitted by XY polynomials for further optimization of an F-theta freeform scanning lens.…”
Section: Applications Of Different Types Of Opticalmentioning
confidence: 99%
“…In this case the problem under consideration was to use a single mirror to solve the single source problem and it was shown that this was equivalent to the mathematical problem of integrating an over-constrained pair of partial differential equations. A sample application of this problem is the design of a driver-side mirror for a motor vehicle, which has no blind-spot and yet provides the observer with a perspective view of the scene [1,4,5].…”
Section: Introductionmentioning
confidence: 99%